THE EFFECT OF ONLINE RESERVATION SYSTEM AND ONLINE CUSTOMER REVIEW TOWARD BRAND IMAGE, TRUST, AND PURCHASE DECISION ON HOSPITALITY BUSINESS INDUSTRY - Falihah, Nurul; Siti, Astuti Endang; Kusdi, Rahardjo; Andriani, Kusumawati (International Journal of Psychosocial Rehabilitation, 2020)
Hotels in Jakarta are having to face very stiff competition. Jakarta’s 5-star Hotel occupancy rate in 2019 was only 55 %. To get more room bookings, hotels provide the online reservation systems as well as the online customer reviews for hotel guests, so they can easily get valuable information from previous guests who have had experience as guests of their chosen hotel. The objective of this study is to analyse the effect of online reservation systems and online customer reviews on brand image, trust and purchase decisions. This research focuses on empirical testing of the model framework using Structural Equation Model (SEM). The study population were all guests who had stayed at ‘X’ Hotel Jakarta using online reservation systems and reading online customer reviews before making a room reservation in September 2019 - February 2020. The research sampling was carried out by using a nonprobability sampling technique and obtaining 200 hotel guests. The results of the study showed that the online reservation systems and online customer reviews significantly affect the brand image, trust and purchase decisions. Trust significantly affects the purchase decisions while brand image insignificantly affects trust and purchase decisions.